2019
DOI: 10.1111/een.12799
|View full text |Cite
|
Sign up to set email alerts
|

Honeydew composition and its effect on life‐history parameters of hyperparasitoids

Abstract: 1. Diets that maximise life span often differ from diets that maximise reproduction. Animals have therefore evolved advanced foraging strategies to acquire optimal nutrition and maximise their fitness. The free‐living adult females of parasitoid wasps (Hymenoptera) need to balance their search for hosts to reproduce and for carbohydrate resources to feed. 2. Honeydew, excreted by phloem‐feeding insects, presents a widely available carbohydrate source in nature that can benefit natural enemies of honeydew‐produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
(89 reference statements)
1
16
0
2
Order By: Relevance
“…Maranello) and winter wheat plants (Triticum aestivum var. Premio) were grown from seeds in a greenhouse using conditions and methods described in van Neerbos et al (2020). Pepper plants were grown individually in pots (1.45 L, 13 cm diameter) and used in experiments 5-6 weeks after sowing.…”
Section: Plants and Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maranello) and winter wheat plants (Triticum aestivum var. Premio) were grown from seeds in a greenhouse using conditions and methods described in van Neerbos et al (2020). Pepper plants were grown individually in pots (1.45 L, 13 cm diameter) and used in experiments 5-6 weeks after sowing.…”
Section: Plants and Insectsmentioning
confidence: 99%
“…Moreover, after parasitized aphids turn into mummies and stop feeding on the plant, they no longer produce honeydew. Instead of directing hyperparasitoids to their host, attraction to honeydew may be driven by the substantial impact of this carbohydrate-rich food source on longevity and fecundity of aphid hyperparasitoids (van Neerbos et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Honeydew composition is an important driver of ant-aphid interactions as well as interactions with predators and parasitoids [3 , 4] . A recent study reported how aphid honeydew composition affects longevity and fecundity on hyperparasitoid wasps, a fourth trophic level insect [5] . Total sugar content in honeydew can be characterized using colorimetric anthrone-sulfuric acid assays [6] though other analytical techniques provide more detailed information on the composition of specific sugars.…”
Section: Introductionmentioning
confidence: 99%
“… [8] Sugars: sorbitol, mannitol, trehalose, glucose, fructose, melibiose, sucrose, melezitose, raffinose, maltose HPLC with ECD 35 2.5 ppm van Neerbos et al. [5] Sugars: glucose, fructose, sucrose, trehalose, melibiose, maltose, isomaltose, maltulose, isomaltulose, melezitose, erlose, raffinose, 1-kestose, isomaltotriose, maltotriose, nidrose, stachyose HPLC with anion exchange column and pulse amperometric detection 25 Not reported Shaaban et al. [9 , 10] …”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence of important declines in insect populations has caused great concern among the scientific community (Biesmeijer et al, 2006;Dirzo et al, 2014;Goulson et al, 2008;Hallmann et al, 2017;Harvey et al, 2020;Potts et al, 2010). Studies carried out in a rainforest of Puerto Rico (Lister and Garcia, 2018) and European protected areas (Hallmann et al, 2017) showed insect biomass losses of more than 75% between 1989 and 2016.…”
Section: Ecosystem Services Provided By Beneficial Insectsmentioning
confidence: 99%